KOMUNIKASI KEPEMIMPINAN KEPALA DESA DALAM PEMBANGUNAN DESA SIMANDOLAK KECAMATAN BENAI KABUPATEN KUANTAN SINGINGI TAHUN 2013-2018 - Permada, Ogesta; Nasution, Belli (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Leadership is a decisive factor in the success or failure of an agency or company he leads. Successful leadership of an agency or government depends on the quality of leadership. Head of village simandolak carry out the mandate of the community to lead and build simandolak village, infrastructure development that has been implemented in the development program year 2013-2018 as a benchmark of its success in building simandolak village benai district kuantan singingi regency. Starting from the construction of concrete rebound roads, farm roads, construction of soccer stadiums, wi-fi networks in the office of the village head simandolak, which serves to facilitate the community in various functions of each development. This study aims to determine: (1) how the leadership of the village head simandolak village Benai district kuantan singingi regency in 2013-2018. (2) how the development communication done by the head of the village simandolak benai district kuantan singingi regency in 2013- 2018 This research uses descriptive qualitative method, with informant selection using purposive sampling technique. Data collection techniques use observation, interview and documentation. The theory that is in use of innovation diffusion from Evereet Rogers. For verification of data use triangulation technique and extension of participation. The results of this study indicate that communication leadership of the Village Head in the village development simandolak running well. Head or village apparatus conveys instructions and information easily understood by the village community simultaneously. In communications the leadership of the village head with the tool, and the villagers are effective, so they can persuade the community in the development program, and may generate new ideas / ideas as the village development program at simandolak Benai districts of Kuantan Singingi Regency in 2013-2018 Keywords: Communication Leadership, Communication Development.